2016
DOI: 10.3391/bir.2016.5.4.10
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of dreissenid biodeposits as a potential food resource for invasive Asian carp

Abstract: This is the first attempt to outline the occurrence of selected invasive alien vertebrates in Greece, since up to now, there are no "official" or scientific reports except from sporadic sightings and anecdotal stories. Records on the occurrence of: Lithobates catesbeianus, Trachemys scripta (T. s. elegans and T. s. scripta), Neovison vison, Myocastor coypus, Nyctereutes procyonoides and Ondatra zibethicus were requested through a pan-Hellenic survey. According to the results, the coypu (Myocastor coypus) appea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 0 publications
1
11
0
Order By: Relevance
“…Furthermore, Anderson et al. () demonstrated that BHC mitigated their weight loss and, in some cases, even gained weight when feeding only on dreissenid biodeposits. This suggests that the beneficial effect of supplementing model diets with detritus simulated by our model was reasonable given that BHC would have access to additional prey resources and a greater abundance of biodeposits in Lake Michigan than the rations fed to them by Anderson et al.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Furthermore, Anderson et al. () demonstrated that BHC mitigated their weight loss and, in some cases, even gained weight when feeding only on dreissenid biodeposits. This suggests that the beneficial effect of supplementing model diets with detritus simulated by our model was reasonable given that BHC would have access to additional prey resources and a greater abundance of biodeposits in Lake Michigan than the rations fed to them by Anderson et al.…”
Section: Discussionmentioning
confidence: 99%
“…For both surface and whole water column scenarios, we ran simulations under three different diets: (1) phytoplankton only; (2) phytoplankton and zooplankton; and (3) phytoplankton, zooplankton, and detritus. We used prey energy density values of 2,600 J/g wet mass, 2,512 J/g wet mass, and 127.3 J/g wet mass for phytoplankton, zooplankton, and detritus, respectively (Anderson et al., , , ). We attributed the energy density of dreissenid mussel biodeposits to all Lake Michigan detritus—assuming that this is the most prevalent detrital food source in the lake (Madenjian, ).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations